Managing and improving a Bank’s profitability and liquidity in times of crisis - Davis-Adesegha, Jennifer (IADITI Editions, 2025)
As banks in recent years have been exposed to a series of crises ranging from the 2008 financial crisis, the Covid-19 pandemic, and now the devastating economic effects of Russia-Ukraine War, a critical analysis of how banks manage and improve their profitability and liquidity during a crisis is essential for discerning the improvement measures that must be adopted. In that context, this study used the integrative review as the methodology for evaluating different theories and literature on the strategies that most contemporary banks use for managing and improving their profitability and liquidity during times of crisis. Outcomes of thematic and narrative analysis of different studies on the strategies for managing and improving a bank’s profitability and liquidity during times of crisis revealed that the major strategies used by most banks encompass maintaining balanced portfolios of liquid assets, liquidity ratio analysis, and stress testing. Other strategies were found to include asset-liability management (ALM), diversification of a bank’s funding sources, a risk-based management approach, and the use of a contingency funding plan. Even if there is no crisis, the outcomes of the integrative review imply that bank crisis management, aimed at managing and improving a bank’s profitability and liquidity, must be part of the organisational culture. It must be part of the organisational culture that improves a bank’s overall resilience and constant preparedness to respond to and withstand all unfolding disruptions and discontinuities. Unfortunately, due to a gap arising from lack of a comprehensive model for managing and improving a bank’s profitability and liquidity during a crisis, most banks were still found to face challenges of discerning how to do so more effectively and comprehensively whenever a crisis erupts. To respond to such a gap, this study proposed the proactive stress testing model for managing and improving a bank’s profitability and liquidity during times of crisis. Such a model not only enriches the existing theories and literature on bank crisis management, but also its adoption will leverage effective mitigation of the crisis’s devastating effects to improve a bank’s overall profitability and liquidity during the crisis, and for a long period after the crisis.
Keywords: Bank Liquidity; Bank Profitability; Bank Risks; Bank Crisis Management